2003
DOI: 10.1037/0022-3514.85.6.1016
|View full text |Cite
|
Sign up to set email alerts
|

On the Behavioral Consequences of Infrahumanization: The Implicit Role of Uniquely Human Emotions in Intergroup Relations.

Abstract: Four experiments confirmed the hypothesis that people discriminate the out-group on the basis of the expression of uniquely human emotions. In Study 1, using a lost e-mail paradigm, the expression of a uniquely human emotion resulted in "nicer" replies when the sender was an in-group compared with an out-group member. The same pattern of results was obtained in Studies 2 and 3 using a conformity paradigm. In addition, perceived similarity was measured and proposed as a potential underlying mechanism (Study 3).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
211
3
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(234 citation statements)
references
References 74 publications
(156 reference statements)
10
211
3
10
Order By: Relevance
“…Vaes and colleagues investigated people's reactions when an outgroup member expressed secondary emotions, examining a range of different situations involving perspective taking , political credibility (Vaes, Paladino, & Magagnotti, 2011), imitation, avoidance reactions (Vaes, Paladino, Castelli, Leyens, & Giovanazzi, 2003), and helping behaviour (Vaes et al, 2003;Vaes, Paladino, & Leyens, 2002). In all these contexts a similar pattern of results was reported that is best demonstrated with an example.…”
Section: Vaes Et Almentioning
confidence: 48%
“…Vaes and colleagues investigated people's reactions when an outgroup member expressed secondary emotions, examining a range of different situations involving perspective taking , political credibility (Vaes, Paladino, & Magagnotti, 2011), imitation, avoidance reactions (Vaes, Paladino, Castelli, Leyens, & Giovanazzi, 2003), and helping behaviour (Vaes et al, 2003;Vaes, Paladino, & Leyens, 2002). In all these contexts a similar pattern of results was reported that is best demonstrated with an example.…”
Section: Vaes Et Almentioning
confidence: 48%
“…Twenty-eight emotional words (eight used as training examples; 20 used in the manipulation check) were pre-tested for their degree of humanity, their valence and the desirability of their expression (e.g., Vaes et al, 2003). As expected, the only main ef-fect was found for humanity, F(1, 24) = 222.67, p < .001, g 2 = .90.…”
Section: Pre-test Of Emotional Wordsmentioning
confidence: 82%
“…To achieve full humanity, these outgroups have to show that they share core similarities (i.e., emotional vocabulary) with the ingroup. The problem is that the proof cannot come from outgroups themselves (e.g., Vaes et al, 2003), but has to be delivered by neutral third parties. Nevertheless, the possibility of humanizing a disliked outgroup is a great step towards harmony between groups.…”
Section: Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…También el uso de sentimientos provocó que los participantes se mostraran más proclives a adoptar la perspectiva de los miembros del endogrupo que del exogrupo (Vaes, Paladino, y Leyens, 2004). De forma complementaria, el impacto de los sentimientos también ha sido analizado en relación a las conductas de acercamiento y evitación (Vaes et al, 2003, estudio 4), mostrando que describir al endogrupo y al exogrupo con sentimientos, facilita las respuestas de acercamiento de los sujetos al endogrupo y de evitación del exogrupo.…”
Section: Las Consecuencias De La Animalización Y La Mecanizaciónunclassified